2019
DOI: 10.3390/jof5040087
|View full text |Cite
|
Sign up to set email alerts
|

The Dysbiosis and Inter-Kingdom Synergy Model in Oropharyngeal Candidiasis, a New Perspective in Pathogenesis

Abstract: As more information emerges on oral microbiota using advanced sequencing methodologies, it is imperative to examine how organisms modulate the capacity of each other to colonize or trigger infection. Most mouse models of oral C. albicans infection have focused on interactions with single bacterial species. Thus, little is known about the microbiome-mediated interactions that control the switch of C. albicans from commensalism to infection. Evidence is accumulating that in immunosuppression where mucosal candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…The presence, composition, and metabolic stage of the resident microbiota may affect the efficacy of Lactobacillus species used as probiotics. For example, while lactobacilli modulate the growth and morphologic transition of Candida in vitro, murine studies show that Candida overgrowth may reduce the abundance of oral lactobacilli, favoring an enterococcus-rich dysbiosis, as recently demonstrated by our group [17,23]. Moreover, Candida may prevent the restoration of the healthy microbiota post-antibiotics, by inhibiting Lactobacillus spp in th murine gut [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence, composition, and metabolic stage of the resident microbiota may affect the efficacy of Lactobacillus species used as probiotics. For example, while lactobacilli modulate the growth and morphologic transition of Candida in vitro, murine studies show that Candida overgrowth may reduce the abundance of oral lactobacilli, favoring an enterococcus-rich dysbiosis, as recently demonstrated by our group [17,23]. Moreover, Candida may prevent the restoration of the healthy microbiota post-antibiotics, by inhibiting Lactobacillus spp in th murine gut [40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, under a dysbiotic scenario, some pathobionts (commensals that can turn into opportunistic pathogens) may form synergistic interactions with each other, leading to severe infections. Recently, Bertolini et al showed that oral bacterial pathobionts facilitate fungal infection by increasing the expression of virulence genes in C. albicans or disrupting the mucosal barrier via proteolytic enzymes [ 23 ]. Hong et al suggested oral microbiota disruption is associated with oral mucositis, exacerbating epithelial injury in cancer patients receiving cytotoxic chemotherapy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common fungal and bacterial species detected in DFU are Candida albicans and Staphylococcus aureus , found in 47 and 95% of DFUs respectively [ 6 8 , 13 , 15 , 16 , 26 , 33 ]. Interactions between these species are synergistic and enabled via cell-cell adhesion and cross-feeding mechanisms [ 34 36 ]. Attachment of S. aureus to C. albicans in biofilms is well studied [ 37 , 38 ] and serve as model for studying cross-kingdom interactions [ 39 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans is the most frequently isolated fungal species in the oral cavity [ 22 ]. Although it is a human commensal species, under certain conditions, such as the use of antibiotics, immunosuppressive treatments or immune-depressive diseases, and reduced salivation, it can cause infections of the oral mucosa [ 23 , 24 , 25 ]. In addition, due to its high capacity to form biofilms, it can colonize abiotic surfaces, such as prostheses and dental implants, being involved in the etiology of peri-implantitis [ 8 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%